Drivetrain modelling and parameter calculation for an electric bus with fixed or 2-speed gearbox. (25th September 2020) - Novak, Martin; Novak, Jaroslav; Morkus, Josef; Musalek, Lubomir; Sivkov, Oleg
This paper presents drivetrain calculations for an electric bus. Parameters of motor, gears and motor efficiency map are used. The goal is to select the suitable motor and gearbox. Driving cycle SORT2 and real life driving cycles measured on bus lines are used. Based on the bus manufacturer assignment, only permanent magnet synchronous machines are considered. The motor output power is considered in the range of 120-160 kW. The selection of axle gear ratios was limited to 6.19, 6.5 and 7.35, as those are readily available. The gearbox was either a fixed one, with gear ratio of 1.8, or a 2-speed gearbox with a gear ratio of 1 and 1.8. The calculations have shown, that a 2-speed gearbox can decrease the energy consumption. The improvement is in the range of 1-3% dependent on the motor option and driving cycle.